Influence of Oral Microbiota on the Presence of IgA Anti-Citrullinated Protein Antibodies in Gingival Crevicular Fluid - de Smit, Menke J.; Rahajoe, Poerwati Soetji; Raveling-Eelsing, Elisabeth; Lisotto, Paola; Harmsen, Hermie J. M.; Kertia, Nyoman; Vissink, Arjan; Westra, Johanna (Frontiers in Oral Health, 2022)
Introduction The relation between rheumatoid arthritis (RA) and periodontitis (PD) has been investigated ever since the discovery of the citrullinating enzyme peptidyl arginine deaminase presents in the oral bacterium Porphyromonas gingivalis. Recently, we demonstrated the presence of RA autoantibodies, especially of IgA anti-citrullinated protein antibody (ACPA), in gingival crevicular fluid (GCF) of Indonesian patients with and without RA or PD which might indicate the local formation of RA antibodies in the periodontium. Aim The purpose of this study was to assess whether the subgingival microbiome is related to the presence of IgA ACPA in the GCF of healthy individuals with or without PD. Patients and Methods Healthy individuals with a known periodontal status and high IgA ACPA (>0.1 U/ml) in GCF (n = 27) were selected and matched for age, gender, periodontal status, and smoking status with 27 healthy individuals without IgA ACPA in their GCF. Taxonomic profiling of the subgingival microbiome was based on bacterial 16S rRNA gene sequencing. Downstream analyses were performed to assess compositional differences between healthy subjects with or without IgA ACPA in GCF and with or without PD. Results Between groups with or without PD, or with or without IgA ACPA in GCF, no differences in alpha diversity were seen. Beta diversity was different between groups with or without PD (p < 0.0001), and a trend was seen in subjects with PD between subjects with or without IgA ACPA in GCF (p = 0.084). Linear discriminant analysis effect size (LEfSe) revealed no significant differences in the total population between subjects with IgA ACPA compared to subjects without IgA ACPA in GCF. Although Porphyromonas was not identified by LEfSe, its relative abundance was significantly higher in healthy individuals with high IgA ACPA in GCF compared to individuals without IgA ACPA in GCF (p = 0.0363). Zooming in on the subgroup with PD, LEfSe revealed that species Neisseriaceae, Tannerella, and Haemophilus were more abundant in the subjects with IgA ACPA in GCF compared to subjects without IgA ACPA in GCF. Conclusion Periodontitis and certain taxa, including Porphyromonas, seem to be associated with the local presence of ACPA in the periodontium.